Effectiveness of Performance Related Pay in Achieving Organizational Goals - Afzal, Umair Shafi (2013)
Reward management being one of the most important determinant of organizational profitability, deciding and managing reward system is one of the most important decision HR managers have to take since it has a significant outcome. Reward system has different elements and Performance Related Pay (PRP) is one of the most important elements in reward management. PRP basically focuses on providing an individual with a financial reward; this financial reward is linked with his individual, group of organization’s performance. Ever since the concept of fixed incremental has raised concerns among managers and professionals, PRP has gained popularity as it helps organizations to achieve their objectives. Due to limited literature review being present on this topic in context to Malaysian companies, this calls for a need to explore this area in detail. The main significance of this research is to examine the role and effectiveness of PRP in achieving organizational goals within the context of Malaysian organizations. This study focuses on seven variables altogether; these are divided into six independent variables which are bonus, commission, salary increments, profit sharing, employee share ownership program and flexible benefits, dependent variable is achievement of organizational goals. A total of four companies from different sectors operating in Malaysia participated in this research. Four semi-structured individual in-depth interviews were conducted with the HR managers of these companies. Questions were divided into two sections, section one focused on the basic information of the person who was interviewed and his company. Section two consisted of nine main questions that were designed from the literature review and they were linked with the objectives of this study. The result of this study revealed that PRP plays a vital role in improving and motivating employees of an organization. They have their individual or departmental goals to achieve for which they are rewarded and these are in-line with the overall organizations objectives. Each and every employee achieving their objectives ultimately leads towards organization attaining their goal which is increase in the profitability and expansion of business. Study also suggests measures for the participating companies to address the issues and challenges they are facing due to PRP.